Spanish adaptation of the Allophilia Scale - Magallares, Alejandro; Morales, Jose Francisco (Anales de Psicología / Annals of Psychology, 2017)
The aim of this study is to adapt and to obtain evidences of validity of the Allophilia Scale to Spanish population. Participants were 960 individuals from all over Spain. Questionnaires to measure prejudice toward North African people, stress and empathy were used to analyze the criterion validity of the Allophilia scale. Confirmatory factor analysis showed that the items of the questionnaire fit a model with five factors, corresponding to the dimensions proposed by the original authors (affection, comfort, kinship, engagement, enthusiasm). Additionally, it has been found that the Allophilia scale is related with other variables such as prejudice toward North African people (cognitive, emotions and behaviors), stress (interaction, resources, identity) and empathy. In light of these results, we conclude that the questionnaire is methodologically valid and can be used by the scientific community to measure cooperative and participatory intergroup behavior and as a complement to traditional measures of prejudice and negative intergroup behaviors.